Mutations of PHOX2B Gene in Patients of Obesity Hypoventilation Syndrome in Central India - Tyagi, Ankita; Goyal, Abhishek; Chaware, Prashant; Rathinam, Bertha A.D. (Journal of Laboratory Physicians, 2021)
Background Paired-like homeobox 2B (PHOX2B) gene on chromosome 4p12 codes for a transcription factor having a role in the formation of noradrenergic neuronal circuits. Its mutations have been linked to congenital central hypoventilation syndrome (CCHS). The clinical presentation of both, obesity hypoventilation syndrome (OHS) and CCHS in adults (named late-onset central hypoventilation syndrome), is quite similar. Because of this symptomatic similarity, multifactorial causation of OHS, the mutation of PHOX2B gene was studied in patients with OHS in this study.Methods A hospital-based cross-sectional study was performed on patients diagnosed with OHS. The deoxyribonucleic acid was extracted from 2 mL of venous blood and was further amplified, specific to exon 3. The amplified products were cast and run in 2% agarose gel and then subjected to Sanger sequencing.Results Thirty patients of OHS (21 male; 9 female) were enrolled in the present study, average age being 51.7 years. The Sanger sequencing of the samples revealed no apparent areas of deletions and no apparent mutations.Conclusion Primers for exon 3 were used for amplification in thermocycler, as exon 3 is the most frequently mutated exon for PHOX2B gene, as per existing literature. The entire gene needs to be studied for mutations and the sample size needs to be increased.
Keywords: obesity hypoventilation syndrome; PHOX2B gene